Hemodynamic Effect of Laser Therapy in Spontaneously Hypertensive Rats - Tomimura, Suely (Sociedade Brasileira de Cardiologia, 2014)
Systemic arterial hypertension (SAH) is considered to be the greatest risk factor for the development of neuro-cardiovascular pathologies, thus constituting a severe Public Health issue in the world. The Low-Level Laser Therapy (LLLT), or laser therapy, activates components of the cellular structure, therefore converting luminous energy into photochemical energy and leading to biophysical and biochemical reactions in the mitochondrial respiratory chain. The LLLT promotes cellular and tissue photobiomodulation by means of changes in metabolism, leading to molecular, cellular and systemic changes. The objective of this study was to analyze the action of low-level laser in the hemodynamic modulation of spontaneously hypertensive rats, in the long term. Animals (n = 16) were randomly divided into the Laser Group (n = 8), which received three weekly LLLT irradiations for seven weeks, and into the Sham Group (n = 8), which received three weekly simulations of laser for seven weeks, accounting for 21 applications in each group. After seven weeks, animals were cannulated by the implantation of a catheter in the left carotid artery. On the following day, the systemic arterial pressure was recorded. The Laser Group showed reduced levels of mean blood pressure, with statistically significant reduction (169 ± 4 mmHg* vs. 182 ± 4 mmHg from the Sham Group) and reduced levels of diastolic pressure (143 ± 4 mmHg* vs. 157 ± 3 mmHg from the Sham Group), revealing a 13 and 14 mmHg decrease, respectively. Besides, there was a concomitant important decline in heart rate (312 ± 14 bpm vs. 361 ± 13 bpm from the Sham Group). Therefore, laser therapy was able to produce hemodynamic changes, thus reducing pressure levels in spontaneously hypertensive rats.